BOS-Q FISHING PARK - Firhan, Firhan; Kasih, Yulizar (Universitas Multi Data Palembang, 2023)
Fishing pond which will be called Bos-Q Fishing Park is a business idea with a fishing pond concept that is unique with Jumbo-sized Fish (Monster) from various species, both local and imported. Bos-Q Fishing Park will also have a Mega Aquatank and a conservation pond specifically for endemic fish native to Indonesia and Palembang which will be made as educational media for visitors to preserve nature, especially in terms of fisheries. For the establishment of this business, the author while the business owner requires an initial capital of Rp. 466,610.00, with 9 workers in it who have their respective job specifications. With the calculated calculations, the initial payback period or PP (Payback Period) of this business is 2 years 9 months 15 days, with an NPV (Net Present Value) of Rp 460,918,475,- and a PI (Profitability Index) index. of 1.99 which is greater than the number 1 makes this business feasible to establish. With an IRR (Internal Rate of Return) of 49% which is a percentage greater than the BI Rate of 3.50% and an ARR (Average Rate of Return) of 112%, it shows that the Bos-Q Fishing Park business is worthy to be established.